PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TOKOPEDIA DI KOTA SEMARANG - D, Wahid Imam; Rodhiyah, Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2016)
The development of the digital world, especially the Internet makes buying or selling online through e-commerce is growing rapidly. This makes many emerging e-commerce offering a variety of services and promotion. However, due to competition between online stores are increasingly stringent, Tokopedia as one of the largest in Indonesia, should strive to become the largest e-commerce in Indonesia, namely by launching a range of services and promotions. This study aims to determine influence of Service Quality (X1) and Promotion (X2) toward Purchasing Decisions at E-Commerce Tokopedia in Semarang City. This type of research is explanatory. Using a combination of accidental and purposive sampling, ie by distributing questionnaires online through google form, and offline by going directly to the field. The total sample is 97 respondents. Measurement scale using Likert scale. In the analysis of the data using validity, reliability, correlation coefficient, multiple linear regression analysis, the determinant coefficient, t test and f test using SPSS. The results show variable service quality and promotion in this study had an influence toward the purchase decision variable partially or simultaneously. Its recommendation is to increase the sales promotion by giving discounts, vouchers, or bonuses. Improving the service quality in terms of the ease of contacting the seller also the ease and speed of a refund if the goods are not appropriate, and improve purchasing decisions through increased customer satisfaction in line with expectations given.